Software Process Improvement and Capability Determination c - O$1 (BConnor, Rory V.s; Rout, Terry; McCaffery, Fergal; Dorling, Alec.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 11th International Conference on Software Process Improvement and Capability Determination, SPICE 2011, held in Dublin, Ireland, in May/June 2011. The 15 revised full papers presented and 15 short papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on process modelling and assessment, safety and security, medi SPICE, high maturity, implementation and improvement.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Bioinformatics; Information Systems; Computer Science; Management of Computing and Information Systems; Software Engineering; Computer Communication Networks; Computational Biology/Bioinformatics.; Computers and Society; Algorithm Analysis and Problem Complexity